The Pre-synaptic Landscape of Mitral/Tufted Cells of the Main Olfactory Bulb - Vinograd, Amit; Tasaka, Gen-ichi; Kreines, Lena; Weiss, Yair; Mizrahi, Adi (Frontiers in Neuroanatomy, 2019)
In olfaction, all volatile odor information is tunneled through the main olfactory bulb (OB). Odor information is then processed before it is transferred to higher brain centers. Odor processing in the OB is carried out by numerous local inhibitory circuits and modulated by top-down input. Top-down modulation of OB function has been shown to act via interneurons but evidence also exists for its direct impact onto the principle mitral and tufted cells (M/Ts). Here, we used monosynaptic rabies trans-synaptic tracing from the OB to map and quantify the local and top-down presynaptic landscape of M/Ts and local inhibitory interneurons. We found that M/Ts receive a significant amount of top-down inputs from various brain regions that matches qualitatively but not quantitatively those that synapse onto local inhibitory inter-neurons. These results show that M/Ts are direct targets of top-down inputs.